Associations between ambient air temperature, low birth weight and small for gestational age in term neonates in southern Israel - Itai Kloog; Lena Novack; Offer Erez; Allan C. Just; Raanan Raz (BMC, 2018)
Abstract Background The increase in ambient temperatures (Ta) and emissions of greenhouse gases over the last century has focused attention on the effects of ambient temperatures on health outcomes. We aimed to investigate the association between Ta and the clinical measures of term low birth weight (tLBW) and small for gestational age (SGA) in singleton term infants using a decade of regional hospital data in southern Israel. Methods We linked all births in Soroka University Medical Center in the southern district of Israel insured by Clalit Health Services with pregnancy Ta estimated by our novel hybrid spatio-temporally resolved prediction model. Logistic regression generalized additive models and general linear models were used, with either tLBW or SGA as the dependent variable, modeling entire pregnancy and trimester-specific Ta adjusting for seasonality, time trend, particulate matter, maternal age, gravidity, parity, ethnicity, sex, poverty index and population density. Results The study population included 56,141 singleton term newborns, with 1716 (3.1%) cases of tLBW and 8634 (15.4%) cases of SGA. The average and the median Ta across the entire pregnancy were 19.9 (SD: 1.77, range: 14.6-24.9) degrees centigrade. The lowest Ta quartile (Ta = < 18.5) was associated with higher risk of tLBW (odds ratio = 1.33, 95%CI 1.11-1.58) while the highest Ta quartile (Ta > =21.3) was not significantly associated with tLBW (odds ratio = 1.17, 95%CI 0.99-1.38), in comparison to the two intermediate quartiles. When analyzing SGA as the dependent variable, the lowest Ta quartile was associated with significantly higher risk of SGA (odds ratio = 1.18, 95%CI 1.09-1.29) while the highest quartile was associated with significantly lower risk of SGA (odds ratio = 0.91, 95%CI 0.84-0.99) in comparison to the two intermediate quartiles. Conclusions Our findings suggest that lower pregnancy Ta may increase the risk of tLBW and SGA, and higher pregnancy Ta may decrease the risk of SGA in singleton term infants in southern Israel.